Inside Russia today - Gunther, John, 1901-1970. (New York : Harper & Row, 1962)
An informal study of post-Stalin Russia--its accessibility, attractions, government and politics, culture, society, foreign relations, and current trends in many of these areas--based on the author's trips to Russia.
Includes index.
Keywords: Soviet Union; Soviet Union